Application of international classification of functioning, disability and health in salat: a scoping review - Irma Ruslina Defi; Intan Sabrina Mohamad; Nuzula Chafidh Al Barqi; Adziqa Ammara Qiantori; Andri Qiantori (Universa Medicina, 2025)
BackgroundSalat has been linked to physical, cognitive, emotional and psychological health benefits. This scoping review classifies the health benefits of salat based on the International Classification of Functioning, Disability, and Health (ICF) conceptual framework. The ICF illustrates how Salat may be used as a multi-modal and multidisciplinary framework to rehabilitate clients with different conditions tailored to their clinical, psychosocial and environmental contexts.PurposeTo conduct a scoping review on the health benefits of salat (muslim prayer) based on the ICF conceptual framework.MethodsA literature review was conducted from February to April 2023 using PubMed, EBSCO, and the Scopus Library databases. Articles published between 2012 and 2023 were retrieved using the following keywords: "impact" OR "effect" OR "health benefit" OR "functional outcome" AND "shalat" OR "Muslim prayer" OR "Salat”. Health benefits of salat were subsequently categorised into five domains of the ICF.ResultsA total of 596 articles were identified through PubMed (404), EBSCO (124), and Scopus (68).  Thirty-one records met the predefined inclusion criteria: 21 original articles, two systematic reviews, five literature reviews, one case study, one case series, and one short report. Salat had positive benefits on the cardiorespiratory, haematological, immunological, mental and neuromuscular functions. Salat may serve as a coping mechanism to reduce stress and depression. The frequency and duration of salat had positive associations with maintaining employment, social support and better quality of life.ConclusionSalat is associated with many health benefits, which can be categorised systematically and summarised using the ICF conceptual framework.